Boys to Men ? - Mark, Frederick; Warrior Educational Films; Media Education Foundation (Horthampton, MA : Media Education Foundation, 2002)
Presents interviews with several teenage boys selected from a group of 32 boys from communities in New Jersey in May 2000. From different ethnic, racial, and class backgrounds these boys speak from their own experiences about teen culture, violence, masculinity, and the meaning of manhood. Additional profiles of three participants made over the course of a year examine the daily challenges they face
Title from title screen
With English subtitles
Keywords: Teenage boys -- New Jersey; Adolescence -- United States; Masculinity -- United States; Parent and teenager -- United States; Violence in men -- United States